Relationship between traumatic war experiences and children's posttraumatic and other stress reactions - Arambašić, Lidija (Array, 1997)
During the war in Croatia children were exposed to many highly traumatic events. Some of those events threatened their own well being, and some jeopardized the well being of their parents, relatives etc. During and after such events people report different kinds of posttraumatic reactions as well as other accompanied symptoms (i.e. anxiety, depression, guilt, fear, psychosomatic symptoms). The aim of this study was to see whether posttraumatic stress reactions, anxiety, depression, psychosomatic symptoms and overall adjustment could be predicted from the exposure to different kinds of traumatic events. Data were collected from 1200 primary school pupils (8-14 yrs). Events were classified into five categories (victimization of family members, general war events including staying in shelter, personal victimization, witnessing victimization and loss of home/being refugee). The results show that witnessing victimization and loss of home/being refugee have the lowest predictive value, while other three kinds of traumatic events are equally predictive for measured children's reactions.